2023
DOI: 10.1002/jsfa.12448
|View full text |Cite
|
Sign up to set email alerts
|

Solidification of concentrated pea protein–pectin mixtures as potential binder

Abstract: BACKGROUND Binders in plant‐based meat analogues allow different components, such as extrudate and fat particles, to stick together. Typically, binders then are solidified to transform the mass into a non‐sticky, solid product. As an option for a clean‐label binder possessing such properties, the solidification behavior of pea protein–pectin mixtures (250 g kg−1, r = 2:1, pH 6) was investigated upon heating, and upon addition of calcium, transglutaminase, and laccase, or by combinations thereof. RESULTS Mixtur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…High stickiness was also shown for a mixture composed of pea protein and sugar beet pectin [16]. Furthermore, it was found that this mixture transitions from a semisolid and sticky material into a non-sticky solid upon use of laccase inducing crosslinks between tyrosine in pea protein and ferulic acid in sugar beet pectin [16]. This resembles the above-mentioned transition of methylcellulose in vegan burger patties and the proteinaceous binder in beef burger patties upon heating [5,13,14].…”
Section: Introductionmentioning
confidence: 56%
See 3 more Smart Citations
“…High stickiness was also shown for a mixture composed of pea protein and sugar beet pectin [16]. Furthermore, it was found that this mixture transitions from a semisolid and sticky material into a non-sticky solid upon use of laccase inducing crosslinks between tyrosine in pea protein and ferulic acid in sugar beet pectin [16]. This resembles the above-mentioned transition of methylcellulose in vegan burger patties and the proteinaceous binder in beef burger patties upon heating [5,13,14].…”
Section: Introductionmentioning
confidence: 56%
“…As such, a concentrated mixture thereof could be used to adhere the aforementioned structured ingredients in a plant-based burger patty. High stickiness was also shown for a mixture composed of pea protein and sugar beet pectin [16]. Furthermore, it was found that this mixture transitions from a semisolid and sticky material into a non-sticky solid upon use of laccase inducing crosslinks between tyrosine in pea protein and ferulic acid in sugar beet pectin [16].…”
Section: Introductionmentioning
confidence: 81%
See 2 more Smart Citations